2018
DOI: 10.1002/pssa.201800379
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Topography, and Optical Properties of Ba‐Doped Mn3O4 Thin Films for Ammonia Gas Sensing Application

Abstract: The fabrication of reliable and cost‐effective gas sensor for low concentrations of toxic gases such as ammonia is still a challenging task, in this work the authors report structural, topography, and optical properties of pure and Ba‐doped Mn3O4 thin films prepared by chemical spray pyrolysis (CSP) as well as its gas sensing performance toward low concentrations of ammonia gas. XRD analyses prove the films have tetragonal spinel structure with a preferred orientation along the direction (103). AFM and SEM mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Such features were relatively similar to those previously reported for Mn 3 O 4 films obtained by PLD and chemical bath deposition . Conversely, spray-deposited Mn 3 O 4 films were composed by densely packed flakes or characterized by a poor morphology control . Mn 3 O 4 films obtained by SILAR, spray pyrolysis, soft templating with block copolymers, microwave calcination, or atomic layer deposition were characterized by the presence of interconnected nanosheets, by a granular morphology, ,,,,,, or by interconnected spherical beads. , …”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Such features were relatively similar to those previously reported for Mn 3 O 4 films obtained by PLD and chemical bath deposition . Conversely, spray-deposited Mn 3 O 4 films were composed by densely packed flakes or characterized by a poor morphology control . Mn 3 O 4 films obtained by SILAR, spray pyrolysis, soft templating with block copolymers, microwave calcination, or atomic layer deposition were characterized by the presence of interconnected nanosheets, by a granular morphology, ,,,,,, or by interconnected spherical beads. , …”
Section: Resultssupporting
confidence: 82%
“…52 Conversely, spraydeposited Mn 3 O 4 films were composed by densely packed flakes 13 or characterized by a poor morphology control. 19 Mn 3 O 4 films obtained by SILAR, spray pyrolysis, soft templating with block copolymers, microwave calcination, or atomic layer deposition were characterized by the presence of interconnected nanosheets, 49 by a granular morphology, 14,20,21,48,50,51,53−55 or by interconnected spherical beads. 56,57 An additional important insight into Mn 3 O 4 nanostructure was gained by TEM analyses on representative samples (Figures 2 and S3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several promising NH 3 sensors reported based on inorganic and organic materials. [73][74][75][76][77][78] There are good room temperature Cu based NH 3 sensors where Mahnaz et al presented a sensor with responses of 11% at 50 ppm of NH 3 and 36.46% at 6 ppm of NO 2 . [79] Faegheh et al presented a sensor with responses of 4.34% at 99 ppm of NH 3 and 7.3% at 6 ppm of NO 2 .…”
Section: Ammonia Gas Sensorsmentioning
confidence: 99%
“…[74,76] It has been reported that a 1% Ba doped Mn 3 O 4 thin film ammonia sensor shows a linear response from 20 to 50 ppm with high sensitivity at an optimum operating temperature of 400 °C. [76] Mn 3 O 4 functionalized with Fe 2 O 3 and ZnO sensors demonstrated detection limits of 2.3 and 2.0 ppm, respectively at an optimum operating temperature of 300 °C. [74] Indeed, this is one of the significant drawbacks of using metal oxide sensors for gas sensing that they need to be operated at high temperature to ensure good sensitivity.…”
Section: Ammonia Gas Sensorsmentioning
confidence: 99%